2022
DOI: 10.1097/ico.0000000000002972
|View full text |Cite
|
Sign up to set email alerts
|

Corneal Pigment Opacity From Face-Down Positioning After Pars Plana Vitrectomy, Treated With Descemet Stripping Only Technique

Abstract: The purpose of this study was to report a case of corneal opacity resulting from pigment deposition after face-down positioning, which was treated with Descemet stripping only (DSO) to enable concurrent pars plana vitrectomy (PPV) for retinal detachment repair. Methods:A 79-year-old man with a history of Fuchs endothelial dystrophy and retinal detachment presented for the repair of recurrent retinal detachment and evaluation of a central corneal opacity. Results:The patient was found to have significant cornea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 6 publications
(9 reference statements)
0
2
0
Order By: Relevance
“…In another adaptation of the technique, Yung et al [29] reported use of DSO to achieve corneal clearance of pigment deposition which had developed after pneumatic retinopexy. In this case a pseudophakic patient with FECD was found to have corneal opacity due to endothelial pigment deposition following a previous pneumatic retinopexy and face down positioning [29]. DSO was performed, facilitating posterior segment visualization to complete a pars plana vitrectomy and scleral buckle treating recurrent retinal detachment.…”
Section: Expanding Roles For Descemet's Stripping Onlymentioning
confidence: 99%
See 1 more Smart Citation
“…In another adaptation of the technique, Yung et al [29] reported use of DSO to achieve corneal clearance of pigment deposition which had developed after pneumatic retinopexy. In this case a pseudophakic patient with FECD was found to have corneal opacity due to endothelial pigment deposition following a previous pneumatic retinopexy and face down positioning [29]. DSO was performed, facilitating posterior segment visualization to complete a pars plana vitrectomy and scleral buckle treating recurrent retinal detachment.…”
Section: Expanding Roles For Descemet's Stripping Onlymentioning
confidence: 99%
“…DSO was performed, facilitating posterior segment visualization to complete a pars plana vitrectomy and scleral buckle treating recurrent retinal detachment. At 6-month postoperative review corneal clearance was maintained within the descemetorhexis [29].…”
Section: Expanding Roles For Descemet's Stripping Onlymentioning
confidence: 99%